A Review of Dietary Prevention of Human Papillomavirus-Related Infection of the Cervix and Cervical Intraepithelial Neoplasia - Chih, Hui Jun; Lee, Andy; Colville, Linda; Binns, Colin (Lawrence Erlbaum Associates, Inc, 2013)
The natural history of cervical cancer suggests that prevention can be achieved by modification of the host's immune system through a nutrient-mediated program. This study reviews the preventive role of dietary intake on cervical intraepithelial neoplasia (CIN) induced by human papillomavirus (HPV). Electronic databases were searched using relevant keywords such as, but not limited to, human papillomavirus infection, cervical intraepithelial neoplasia, lifestyle factors, nutrients intake, and diet. High consumption of fruit and vegetables appears to be protective against CIN. The findings also highlight the possibility of consuming high levels of specific nutrients, vitamins, and minerals, and retaining sufficient level of these elements in the body, especially those with high antioxidants and antiviral properties, to prevent progression of transient and persistent HPV infections to high-grade CIN 2 and 3 (including in situ cervical cancer). The protective effect is not significant for high-risk HPV persistent infections and invasive cervical cancer. Although it appears that intake of specific nutrients, vitamins, and minerals may be good in CIN prevention, there is lack of evidence from controlled trial to confirm this. Health professionals shall focus on implementation of a balanced-diet prevention strategy at an early stage for cervical cancer prevention.